Isolation of antagonistic bacterial strains against fungi - Karimov, H.; Azimova, N.; Khaytbayeva, N.; Kobilov, F.; Khamidova, K.; Shukurov, O.; Razzokov, J. (Regulatory Mechanisms in Biosystems, 2024)
This study focused on isolating and identifying antagonistic bacterial strains from diseased vegetable crops and evaluating their potential as biocontrol agents against phytopathogenic fungi. Samples were collected from tomato, sweet pepper, and potato plants across various regions of Uzbekistan. Several bacterial strains were identified using morphological, molecular, and biochemical analyses, with Bacillus licheniformis 6.25 emerging as the most potent antagonist. Molecular characterization through 16S rRNA sequencing confirmed a 99.86% similarity to known B. licheniformis species. The antagonistic activity of B. licheniformis 6.25 was tested against Fusarium solani, Alternaria alternata, and Verticillium dahliae. The strain suppressed fungal growth by over 50%, demonstrating strong antifungal properties. Metabolite analysis via GC-MS revealed bioactive compounds with antifungal, anti-inflammatory, and antimicrobial effects. Antifungal assays showed inhibition zones of 26 mm against A. alternata and 21 mm against F. solani. These findings highlight the potential of B. licheniformis 6.25 as a biocontrol agent for sustainable agriculture and pharmaceutical applications.